2024
DOI: 10.1001/jamainternmed.2023.6638
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Daily Toothbrushing and Hospital-Acquired Pneumonia

Selina Ehrenzeller,
Michael Klompas

Abstract: ImportanceHospital-acquired pneumonia (HAP) is the most common and morbid health care–associated infection, but limited data on effective prevention strategies are available.ObjectiveTo determine whether daily toothbrushing is associated with lower rates of HAP and other patient-relevant outcomes.Data SourcesA search of PubMed, Embase, Cumulative Index to Nursing and Allied Health, Cochrane Central Register of Controlled Trials, Web of Science, Scopus, and 3 trial registries was performed from inception throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 66 publications
0
3
1
1
Order By: Relevance
“…While thick liquids may be harder to clear when aspirated, they may also minimize the frequency and/or volume of aspiration, which could explain the decreased risk of intubation that we found. Furthermore, prior studies have suggested that other factors (eg, oral hygiene and immune status) may be important in the pathogenesis of aspiration pneumonia . Unlike previous studies, we did not find differences between thin and thick liquids with regard to dehydration.…”
Section: Discussioncontrasting
confidence: 98%
“…While thick liquids may be harder to clear when aspirated, they may also minimize the frequency and/or volume of aspiration, which could explain the decreased risk of intubation that we found. Furthermore, prior studies have suggested that other factors (eg, oral hygiene and immune status) may be important in the pathogenesis of aspiration pneumonia . Unlike previous studies, we did not find differences between thin and thick liquids with regard to dehydration.…”
Section: Discussioncontrasting
confidence: 98%
“…Increasing evidence has underscored the association between oral and systemic health. Separation of the 2 makes little sense physiologically or fiscally .…”
Section: Discussionmentioning
confidence: 99%
“…Für das im deutschsprachigen Raum alternativ verwendete Octenidin gibt es nur wenige Studien [8]. Eine aktuelle Metaanalyse konnte zeigen, dass tägliches Zähneputzen zu signifikant weniger HAP-Ereignissen führte [11]. Dieser Effekt konnte insbesondere bei VAP-Patienten nachgewiesen werden.…”
Section: Rolle Von Chlorhexidin-lösungen Im Rahmen Der Mundpflegeunclassified